2017
DOI: 10.1089/cyber.2016.0247
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Social Comparison and Self-Objectification in Mediating Associations Between Facebook Use and Emergent Adults' Psychological Well-Being

Abstract: Although Facebook was created to help people feel connected with each other, data indicate that regular usage has both negative and positive connections to well-being. To explore these mixed results, we tested the role of social comparison and self-objectification as possible mediators of the link between Facebook use and three facets of psychological well-being: self-esteem, mental health, and body shame. Participants were 1,104 undergraduate women and men who completed surveys assessing their Facebook usage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
106
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(115 citation statements)
references
References 53 publications
4
106
0
5
Order By: Relevance
“…Moreover, the tendency to engage in social comparisons on SNSs, regardless of the direction of the comparison (e.g., upward), is associated with poorer well-being. Specifically, engaging in social comparison on SNSs in general (Hanna et al, 2017) and on Facebook (Lee, 2014) is linked with poorer self-esteem and greater depressive and anxiety symptoms. Social comparison on Instagram is linked with poorer self-esteem (Stapleton, Luiz, & Chatwin, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the tendency to engage in social comparisons on SNSs, regardless of the direction of the comparison (e.g., upward), is associated with poorer well-being. Specifically, engaging in social comparison on SNSs in general (Hanna et al, 2017) and on Facebook (Lee, 2014) is linked with poorer self-esteem and greater depressive and anxiety symptoms. Social comparison on Instagram is linked with poorer self-esteem (Stapleton, Luiz, & Chatwin, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies investigating adolescent use of social media focus on the impact of psychological well-being. The results from these studies have found unfavorable effects, especially related to posting and viewing photos, of social media use on mental health, including: negative mood self-objectification, body dissatisfaction, social comparison, eating behaviors, decreased self-esteem, weight dissatisfaction, drive for thinness, and peer competition [9][10][11][12][13][14][15][16][17][18][19]. Even "fitspiration" images and posts that aim to inspire people to live healthy and fit lifestyles reinforce the over-valuation of physical appearance, eating concerns, and excessive exercise that could have serious negative implications on adolescents psychological and emotional health [20].…”
Section: Introductionmentioning
confidence: 99%
“…Facebook, the largest social media network, currently has approximately 2 billion monthly users , corresponding to more than 25% of the world's population. While the existence of an online social network may seem harmless or even beneficial, a series of recent studies have suggested that use of Facebook and other social media platforms may have a negative influence on mental health .…”
mentioning
confidence: 99%
“…This aspect remains unclear, but an intuitively logical explanation—with some empirical support—is that people predominantly display the most positive aspects of their lives on social media and that other people—who tend to take these positively biased projections at face value—therefore get the impression that their own life compares negatively to that of other Facebook users . As indicated by the recent findings by Hanna et al, such upward social comparison is very likely to mediate the negative effect of Facebook use on mental well‐being .…”
mentioning
confidence: 99%
See 1 more Smart Citation